Unraveling the effects of sulfamethoxazole on the composition of gut microbiota and immune responses in Stichopus variegatus - Tan, Chunming; Zhao, Wang; Wen, Weigeng; Chen, Xu; Ma, Zhenhua; Yu, Gang (Frontiers in Microbiology, 2022)
The aim of this work was to reveal the changes in gut microbiota composition and immune responses of sea cucumber (Stichopus variegatus) after being affected by different doses of sulfamethoxazole. In this study, the bacterial 16S rRNA of gut microbiota were analyzed by high-throughput sequencing, and the activities of immune enzymes (lysozyme [LZM], phenoloxidase [PO], alkaline phosphatase [AKP] and acid phosphatase [ACP]) in the gut of S. variegatus were determined. The results showed that the gut microbiota presented a lower richness in the antibiotic treatment groups compared with the control group, and there were significant differences among the dominant bacteria of different concentration treatments. At the genus level, the abundance of Escherichia, Exiguobacterium, Acinetobacter, Pseudomonas, and Thalassotalea were significantly decreased in the 3 mg/L treatment group, while Vibrio was significantly increased. Furthermore, the 6 mg/L treatment group had less effect on these intestinal dominant bacteria, especially Vibrio. The changes in relative abundance of Vibrio at the species level indicated that lower concentrations of sulfamethoxazole could enhance the enrichment of Vibrio mediterranei and Vibrio fortis in S. variegatus more than higher concentrations of sulfamethoxazole. Meanwhile, the 3 mg/L treatment group significantly increased the activities of PO, AKP and ACP, and decreased the activity of LZM. These results suggested that lower doses of sulfamethoxazole have a greater effect on the gut microbiota composition and immune responses in S. variegatus and may increase the risk of host infection.